Aerobic composting and enrichment of ayurvedic waste - Lekshmisree C S (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 2003)
The study on "Aerobic Composting of Ayurvedic Waste" was conducted at College of Horticulture, Vellanikkara during the period 2001-2003, to investigate the basic physico-chemical properties of Oushadhi waste material, standardize . formulations of enriched compost from the waste material and also to determine the effect of compost on plant and soil. . The waste material for the .study was collected from the manufacturing unit of Oushadhi pharmaceuticals l6c~d at Kuttanelloor, 8 km east of Thrissur. The factory produced nearly 1 tonne of waste per day during the manufacture of various products like Lehyam, Arishtam, Choomam, Kalkam etc. Hence the safe disposal of these wastes was a serious problem. A preliminary study was conducted to confirm the basic physico-chemical properties of the waste material for a period of 6 months by taking composite samples from the factory at an interval of 10 days. Temperature, pH, microbial count, colour, odour and consistency as well as the major nutrient contents of the waste material were analysed during the time period. Then the waste material were categorised into three substrates namely unsieved (01), 4 mm sieved (02) and 2 mm sieved (03) fractions. Then each substrate was enriched with organic and inorganic enrichers at different levels. The organic enrichers used were cowdung, poultry manure and neemcake each at 5, 10 and 15 per cent of substrate and also their mixtures. The study involved aerobic composting of enriched treatment combinations in pots of size 30 x 32 cm2. Temperature was measured daily and other parameters like pH, dehydrogenase activity and C: N ratio were monitored at 10 days interval throughout the composting process. The end phase of the bioprocessing was arrived at through indications on stabilisation of temperature, pH and the quality of material. Nutrient quality of the composted waste material was arrived at by analysing the content of N, P and K at initial and [mal stages of comp 0 sting.